Love in philosophy. An ethical - aesthetical perspective - Wilfrido Zúñiga-Rodríguez; Omar Julián Álvarez-Tabares (Universidad del Magdalena, 2017)
The world entails and demands that we understand the experience and perception of life from ethical and aesthetic dimensions based on philosophical assumptions. One of such assumptions is that our inhabiting and staying in the world can be made a work of art in perspectives of love. Love is thus constituted as an event for man who finds again the conciliatory spirit of the divine in all things, events and phenomena in his life. This perspective allows him to reach, as far as possible, a response to the question: Who am I?, a question that philosophy has tried to answer by means of categories such as: Beauty, Goodness and Truth based on philosophical and theological criteria.